Tele-Nursing in Post-Operative Care: Expanding Accessibility and Reducing Readmission Ratesh - Catur Budi Susilo; Siri Lek; Pong Krit (Yayasan Adra Karima Hubbi, 2025)
Post-operative care is critical for ensuring optimal recovery, preventing complications, and reducing hospital readmission rates. Traditional follow up methods often face limitations, including geographic barriers, limited access to healthcare providers, and resource constraints, which can compromise patient outcomes. Tele-nursing offers a promising solution by delivering remote monitoring, education, and guidance, thereby enhancing accessibility and supporting continuity of care. This study investigates the effectiveness of tele-nursing interventions in post-operative care, focusing on patient outcomes, adherence to care protocols, and readmission rates. A mixed-methods approach was employed, integrating quantitative analysis of clinical metrics and readmission data with qualitative assessments of patient and nurse experiences. Data were collected from 180 post-operative patients across multiple surgical departments who received tele-nursing support over a 90 day period. Results indicated that tele-nursing significantly reduced 30 day readmission rates, improved adherence to post-operative care instructions, and increased patient satisfaction. Nurses reported enhanced ability to monitor patient recovery, provide timely interventions, and offer personalized education remotely. The study concludes that tele-nursing is an effective strategy to expand access to post-operative care, improve patient outcomes, and reduce healthcare system burden.